Host genetics, phenotype and geography structure the microbiome of a foundational seaweed. Issue 7 (19th February 2022) - Wood, Georgina; Steinberg, Peter D.; Campbell, Alexandra H.; Vergés, Adriana; Coleman, Melinda A.; Marzinelli, Ezequiel M.
Abstract: Interactions between hosts and their microbiota are vital to the functioning and resilience of macro‐organisms. Critically, for hosts that play foundational roles in communities, understanding what drives host–microbiota interactions is essential for informing ecosystem restoration and conservation. We investigated the relative influence of host traits and the surrounding environment on microbial communities associated with the foundational seaweed Phyllospora comosa . We quantified 16 morphological and functional phenotypic traits, including host genetics (using 354 single nucleotide polymorphisms) and surface‐associated microbial communities (using 16S rRNA gene amplicon sequencing) from 160 individuals sampled from eight sites spanning Phyllospora's entire latitudinal distribution (1, 300 km). Combined, these factors explained 54% of the overall variation in Phyllospora's associated microbial community structure, much of which was related to the local environment (~32%). We found that putative "core" microbial taxa (i.e., present on all Phyllospora individuals sampled) exhibited slightly higher associations with host traits when compared to "variable" taxa (not present on all individuals). We identified several key genetic loci and phenotypic traits in Phyllospora that were strongly related to multiple microbial amplicon sequence variants, including taxa with known associations to seaweed defence, disease and tissue degradation. This information on how host‐associated microbial communities vary with host traits and the environment enhances our current understanding of how "holobionts" (hosts plus their microbiota) are structured. Such understanding can be used to inform management strategies of these important and vulnerable habitats.